Tips and Tricks for Making Examination in Moodle - Vámosi, Attila (International Journal of Engineering and Management Sciences, 2017)
Electronic exams made with the Moodle system can greatly facilitate the examiners job, but only few people use this option. This paper will review the examination system of the Moodle, the uploading of the question bank, the creating of the test, and the range of the available statistics. Then answers some frequently asked questions and misunderstandings, and give tips and show tricks related to secure examinations.